Python for Data Science Complete Video Course (Video Training) - Behrman, Kennedy; Gift, Noah (Addison-Wesley Professional, 2019)
9+ Hours of Video Instruction While there are resources for Data Science and resources for Machine Learning, there's a distinct gap in resources for the precursor course to Data Science and Machine Learning. This complete video course fills that gap--it is specifically designed to prepare students to learn how to program for Data Science and Machine Learning with Python. This is the antidote to the over-complicated universe of these hot new, growing technologies. With this course, students will learn the fundamentals of Python and get prepared specifically for Data Science. Noah Gift and Kennedy Behrman take students with zero programming background through enough Python to prepare them for their Data Science curriculum. Companies are looking for developers who can create insight-driven systems, as they are now becoming critical to business success. Very few professionals are adequately trained to handle both large-scale software engineering and Machine Learning/AI. This is an emerging field, and we are developing the training to meet this need in the marketplace. Description Notebook-based Data Science programming in Python is the emerging standard but there is a dearth of quality training material available for beginners. This 9-hour video provides foundational training on the Python language for the novice or beginner programmer looking to start in the Data Science field. The video serves as the 100-level course for a Data Science undergraduate or graduate program. The course has been designed around Colab notebook-based learning. Students would be able to run every exercise shown in the videos. The material focuses on a smaller, easier subset of Python that is needed just for Data Science coding. Skill Level Beginner What You Will Learn Learn Google Colab notebook Data Science programming Learn the essential subset of Python used in Data Science Learn to manipulate data using popular Python libraries such as pandas and numpy Learn to apply Python Data Science recipes to real-world projects Learn functional programming fundamentals unique to Data Science Who Should Take This Course Complete beginners to programming Statisticians and Analysts in the data industry looking to use Python for Data Science Sales, Product Managers, Data Analysts, Marketing who want to perform Data Science Software Engineers looking to level up into Data Science and Machine Learning tracks Students enrolled in a Data Science program Course Requirements General comp ...